1996
DOI: 10.1007/bf02247387
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the acute behavioral effects of flunitrazepam and triazolam in healthy volunteers

Abstract: Flunitrazepam is an hypnotic benzodiazepine marketed in different European countries. Epidemiological studies have shown that it is frequently abused by opioid addicts. In a survey, "liking" scores for flunitrazepam in methadone maintenance patients were higher than ratings for other benzodiazepines. A double-blind, placebo controlled, crossover clinical trial was conducted to assess the acute behavioral effects of flunitrazepam (0.50 and 2 mg) and triazolam (0.25 and 0.50 mg) in healthy male volunteers. Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
(35 reference statements)
4
19
0
2
Order By: Relevance
“…On the other hand, MDMA also reverted the effects of alcohol on the ARCI-BG, increasing the scores above those obtained after MDMA alone administration. This scale is a recognized measure of intellectual efficiency, and the administration of amphetamines or other stimulants increases the scores (Camí et al, 2000a), whereas the administration of sedatives as benzodiazepines or alcohol decrease the scores (Farré et al, 1996(Farré et al, , 1997Holdstock and de Wit, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MDMA also reverted the effects of alcohol on the ARCI-BG, increasing the scores above those obtained after MDMA alone administration. This scale is a recognized measure of intellectual efficiency, and the administration of amphetamines or other stimulants increases the scores (Camí et al, 2000a), whereas the administration of sedatives as benzodiazepines or alcohol decrease the scores (Farré et al, 1996(Farré et al, , 1997Holdstock and de Wit, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This task is a direct measure of the extraocular musculature relaxation and indirect measure of central sedation. The administration of sedatives such as benzodiazepines or ethanol induced exophoria (Farré et al, 1993(Farré et al, , 1996, whereas the administration of stimulants as amphetamine or MDMA produced esophoria (Camí et al, 2000a). These findings suggest that MDMA can reduce the sedation associated to alcohol administration.…”
Section: Discussionmentioning
confidence: 99%
“…The six drug conditions were as follows : ßunitrazepam 1, 2, and 4 mg (Rohipnol, Laboratorios Roche, S.A., Madrid, Spain), triazolam 0.5 and 0.75 mg (Halcion, Upjohn Farmoquímica, Madrid, Spain), and placebo (lactose). The doses of ßunitrazepam and triazolam were selected according to previous studies in healthy volunteers (Farré et al 1996). Drugs were supplied by the Pharmacy Department of Hospital del Mar as identically appearing opaque white soft-gelatin capsules.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…In a study in healthy volunteers (Farré et al 1996), ßunitrazepam induced statistically signiÞcant increases in some pleasurablerelated subjective e¤ects (liking, good e¤ects, high) that may be related to its abuse potential. This study was designed to assess the acute subjective and psychomotor e¤ects of ßunitrazepam in methadonemaintained patients.…”
Section: Introductionmentioning
confidence: 98%
“…At 24 h after administration, abuse potential ratings for flunitrazepam were greater than placebo Griffiths 1998, 2005). Similarly, at doses ranging up to 2 mg, Farre et al (1996) found significantly increased rating scores on items related to abuse potential ("like drug", "good effects") compared to placebo. Furthermore, the 2-mg dose produced the greatest level of disruption in psychomotor performance (reaction time, balance, and digit symbol substitution).…”
mentioning
confidence: 91%